2003
DOI: 10.1002/chin.200322165
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Isoxazoles and Quinoxalines as Potential Anticancer Agents.

Abstract: 12 examples) are synthesized from chalcones (I) and evaluated for their biological activity. Some compounds show significant antibacterial, e.g. (IVc), and compound (IIb) shows significant anticancer activity. -(VEKARIYA, N. A.; KHUNT, M. D.; PARIKH*, A. R.; Indian J. Chem., Sect. B: Org. Chem. Incl. Med. Chem. 42 (2003) 2, 421-424; Dep. Chem., Saurashtra Univ., Rajkot 360 005, India; Eng.) -M. Kowall 22-165

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Compounds (63,64) bearing hydroxyl group at meta or para position of 2-and 6-phenyl rings in combination with 2-furyl, 2-thienyl, or 3-thienyl moiety at 4-position of central pyridine showed significant topo II inhibitory activity and cytotoxicity [84]. In addition, trihydroxylated derivatives are more potent topoisomerase II inhibitors and cytotoxic agents in comparison to dihydroxylated derivatives and similar author also reported topoisomerase II inhibition and cytotoxic potential of monohydroxylated pyridine derivatives (64,65). Amongst all trihydroxy derivates of pyridine proved to be the most potent agents against topoisomerase II and cytotoxicity [85,86].…”
Section: Analogues Of Chalcones Pyrazoline Analogues With Various Phamentioning
confidence: 67%
See 1 more Smart Citation
“…Compounds (63,64) bearing hydroxyl group at meta or para position of 2-and 6-phenyl rings in combination with 2-furyl, 2-thienyl, or 3-thienyl moiety at 4-position of central pyridine showed significant topo II inhibitory activity and cytotoxicity [84]. In addition, trihydroxylated derivatives are more potent topoisomerase II inhibitors and cytotoxic agents in comparison to dihydroxylated derivatives and similar author also reported topoisomerase II inhibition and cytotoxic potential of monohydroxylated pyridine derivatives (64,65). Amongst all trihydroxy derivates of pyridine proved to be the most potent agents against topoisomerase II and cytotoxicity [85,86].…”
Section: Analogues Of Chalcones Pyrazoline Analogues With Various Phamentioning
confidence: 67%
“…Solankee et al reported the synthesis of series of substituted isoxazolines and these were screened for antimicrobial activity against gram-positive, gram-negative bacteria and fungal strains, compound 53 has shown good activity against all the strains which states that compound having methoxy, chloro and nitro groups are more potent as compared to others [64]. Benzimidazole isoxazole were synthesized and screened for antimicrobial and anticancer activity and compound 54 has shown 18-25 mm zone of inhibition against antimicrobial strains and isoxazole moiety bearing molecule showed better anticancer activity [65]. Combrestatin analogues having five membered heterocycles (isoxazole, isoxazoline, oxadiazole) were synthesized and evaluated for cytotoxicity and their ability to inhibit the tubulin assembly.…”
Section: Analogues Of Chalcones Pyrazoline Analogues With Various Phamentioning
confidence: 99%
“…The reaction of chalcones with hydroxylamine hydrochloride can also be performed in the presence of NaOAc and glacial acetic acid to give 3,5diarylisoxazoles [92,93]. Using the same conditions, the condensation of benzimidazolyl-, benzofuranyl-, indolyl-and quinoxalinyltype chalcones with hydroxylamine hydrochloride provided, respectively, benzimidazolyl- [94], benzofuranyl- [95], indolyl- [96] and quinoxalinyl-isoxazoles [97].…”
Section: Transformation Of Chalcones To Isoxazolesmentioning
confidence: 99%
“…H 2 SO 4 (2 drops) for 30 minutes. The product obtained was filtered, dried and recrystallized from ethanol 21 Metal estimation: Metal estimation for Cu(II), Co(III) and Fe(III) complexes was done by incineration method. The metal complexes were taken in a silica crucible.…”
Section: Synthesis Of 2-benzoyl-3-nitrophenyl Quinoxalinementioning
confidence: 99%